PERKEMBANGAN RISET OPERASI DAN MODELNYA - Lokot Muda Harahap; Ahmad Hafiz Nasution; Yulia Rahma; Ryan Alfandi; Putri Elma; Rizky Mardewina; Jesavael Nico Voellers Silaban (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to understand and identify the development of operations research and its model as a problem solving technique. Operations research can be seen as a combination of art and science. The science lies in the use of mathematical techniques and algorithms to solve problems, while as an art, the success of this mathematical model solution is very dependent on the creativity and ability of the decision maker in solving the problem. Data were collected from articles and national journals published in the last 5 years, with related keywords such as